2000
DOI: 10.1002/1096-9861(20001120)427:3<428::aid-cne9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mRNAs encoding the arylhydrocarbon receptor, arylhydrocarbon receptor nuclear translocator, and arylhydrocarbon receptor nuclear translocator-2 in the rat brain and brainstem

Abstract: Dioxin exposure alters a variety of neural functions, most likely through activation of the arylhydrocarbon receptor (AhR) pathway. Many of the adverse effects, including disruption of circadian changes in hormone release and depressed appetite, seem to be mediated by hypothalamic and/or brainstem neurons. However, it is unclear whether these effects are direct or indirect, because there have been no comprehensive studies mapping the expression of components of the AhR pathway in the brain. Therefore, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 45 publications
4
66
0
Order By: Relevance
“…For example, CAR and PXR are expressed highly in the liver, but at low levels in the brain, whereas PPARβ and δ, RXRβ and AhR may be expressed more highly in the brain than in the liver. 153,154 The expression of these nuclear receptors also varies among brain regions. For example, CAR was detectable only in the human caudate nucleus; 155 PXR was expressed at highest levels in the human thalamus, pons and medulla; 156 PPAR and RXR were expressed highly in the rat brainstem but at low levels in the substantia nigra; 157 and AhR was expressed highly in the rat olfactory cortex but at low levels in the amygdala.…”
Section: Mechanisms Of Brain Cyp Inductionmentioning
confidence: 99%
“…For example, CAR and PXR are expressed highly in the liver, but at low levels in the brain, whereas PPARβ and δ, RXRβ and AhR may be expressed more highly in the brain than in the liver. 153,154 The expression of these nuclear receptors also varies among brain regions. For example, CAR was detectable only in the human caudate nucleus; 155 PXR was expressed at highest levels in the human thalamus, pons and medulla; 156 PPAR and RXR were expressed highly in the rat brainstem but at low levels in the substantia nigra; 157 and AhR was expressed highly in the rat olfactory cortex but at low levels in the amygdala.…”
Section: Mechanisms Of Brain Cyp Inductionmentioning
confidence: 99%
“…Because the aryl hydrocarbon receptor (AhR) is ubiquitously distributed in various brain regions including the hypothalamus (Petersen et al 2000), and TCDD enters and distributes in the brain tissue from the blood circulation (Kakeyama et al 2003), it is reasonable to speculate that TCDD affects the GnRH surge-generating mechanism and elicits its toxicity by activating the AhR pathway. Other studies showed that TCDD distributed at the CNS exerts neurotoxicological effects: a high TCDD dose (10 mg/kg) administered to rats was shown to reduce LH secretion and the number of ova at ovulation (Petroff et al 2001).…”
Section: Figurementioning
confidence: 99%
“…Members of the AhR signaling pathway are expressed in the preoptic area of the brain (POA), a region known to control reproductive functions (Petersen et al 2000). The distribution pattern of AhR gene expression closely overlaps with that of glutamic acid decarboxylase (GAD) 67, the enzyme necessary for gamma-aminobutyric acid (GABA) synthesis.…”
Section: Ahr and The Regulation Of The Hypothalamopituitary-gonadal (mentioning
confidence: 99%